The Effect Of Substitution Of Chicken Meat With White Oyster Mushrooms On The Characteristics tum Ayam - Widya Anggraeni, Ni Putu; Suter, I Ketut; Ngurah Anom Jambe, Anak Agung Gede (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2018)
The aims of this research  was to find out the effect of substitution of  chicken meat with white oyster mushrooms on the characteristics of tum ayam, and to find out the exact substitution of chicken meat with white oyster mushrooms that can produce tumayam with the best characteristics. This research used a completely randomized design with treatments such as comparison between chicken meat and white oyster mushrooms i.e : 100% chicken meat : 0% white oyster mushrooms, 90% : 10%, 80% : 20%, 70% : 30%, 60% : 40%, 50% : 50%, 40% : 60% respectively. Sensory evaluation data were analyzed using a randomized block design. Each treatment was repeated three times to obtain 21 units of experiments. Data were analyzed by analysis of variance and if there is a treatment effect, then continued with Duncan test. The results showed that substitution treatment of chicken meat with white oyster mushrooms give the significant effect to moisture content, ash content, protein content, fat content, crude fiber content, color, aroma, flavor, texture (score and hedonic experiment), and the entrie acceptance of tum. Treatment that produces tum  with the best characteristics is that the substitution 60%  chicken meat : 40% white oyster mushrooms, with the results of the analysis of water content 58,02%, ash content 1,35%, protein content 10,46%, fat content 17,09% carbohydrate content 13,08%, crude fiber content 11,66%, the color (hedonic) 4,80 ordinary, the texture (hedonic) 4,60 ordinary, the texture (skor) 4,07 soft, the flavor (hedonic) 5,27 rather like, the taste (hedonic) 5,33 rather like, and overall acceptance (hedonic) 5,27 rather like.